Peningkatan Kemampuan Menulis Laporan Kegiatan Mahasiswa Di Lingkungan Universitas Lancang Kuning - Rosman H Rosman H; Nining Sudiar; Hadira Latiar (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2020)
Activity reports are one of the most important elements in an organization. The activity of writing student activity reports at the end of the implementation of activities becomes a thing that is always avoided by students, especially students who are members of a sub-campus organization. The community service activities aim to provide understanding, as well as improve the ability to write reports on student activities in accordance with the guidelines issued by BPM the Lancang Kuning University. In particular, this activity aims to improve the knowledge and techniques of writing and the preparation of student activity reports especially Organisasi Mahasiswa (ORMAWA) such as DPM, BEM, UKM and HMJ at the Lancang Kuning University. This service activity includes training or counseling which contains the delivery of information for material that is technical and the practice of the report writer, in this case is material about the concept of the report; dialogical method that is question and answer and continues with the practice of writing reports on how to write reports in accordance with the guidelines issued by BPM Lancang Kuning University; and training methods to instill technical and practical skills and skills in writing reports.